Learning styles inventory : A diagnostic questionnaire for construction - Syed Khuzzan Alhabshi, Sh Mazlina; Alshawi, Mustafa; Goulding, Jack (2010)
Learning styles theory is widely acknowledged amongst educational theorists. However, there is little research evidence on the adoption and adaptation of learning styles in an e-Learning environment, specifically in respect of personalised learning environments. In this context, evidence identifies that the more thoroughly instructors understand the differences in learning styles, the better chance they have of meeting the diverse learning needs of learners. In this respect, providing learners with learning environments that suit their learning style can have a positive impact on learning effectiveness. Many learning styles inventories/instruments have attempted to augment learners’ learning styles with learning methods, albeit without taking on board the criticism levied at inventories and similar instruments in terms of reliability and validity (including the rubrics behind the models of learning styles). This paper identifies the process of amalgamating three existing models of learning styles (Kolb; Honey and Mumford; and Felder and Solomon), into a ‘Diagnostic Questionnaire’ learning style inventory for reflection and discussion.